Short-term impact of the 2018 national minimum wage legislation on household income in South Africa - MWENYI, Micheal (KDI School, 2023)
Does the introduction of a national minimum wage policy in South Africa address the income inequality gap by increasing the household income? This paper utilizes a 6-wave panel developed from the Labor Market Dynamics in South Africa dataset which is compiled annually from the Quarterly Labor Force Survey between 2018 and 2019, the year the policy came into effect in South Africa, to contribute to the existing knowledge gap in developing countries. I employed the Difference in Differences (DID) estimation model to examine the short-term impact of South Africa’s national minimum wage policy on household income in both informal and formal sectors. With a 5 percent increase relative to the prevailing average sectoral wages implied by the national minimum wage legislation, my findings suggest that the introduction of the national minimum wage in South Africa had positive effects on household income. However, the increase in real average wage had negative effects on contract employment especially among male employees. There were generally no registered significant effects on hours of work. The outcomes imply that the enactment of a national minimum wage policy leads to a rise in household income, but with minimal detected negative effects towards employment, there must be clear discipline on annual increases of the minimum wage to avoid surging an already existing problem of unemployment in South Africa.
Thesis(Master) -- KDI School: Master of Development Policy, 2023
Keywords: Income distribution--South Africa; Minimum wage--South Africa; Wages--Government policy--South Africa